Uzbek Art and Culture is the Image of the State - Ziyodakhan, Togonbayeva; Mominmirza, Kholmo’minov (International Journal on Orange Technologies, 2023)
In this article, the history of Uzbek art and its importance today, the role of art and culture, the art of gatekeeping and the shortcomings of this art are given.